Nadwaga i otyłość sześcioletnich dzieci miejskich i wiejskich = Excess weight and obesity in 6 year old children from urban and rural areas - Trzcińska, Dorota; Świderska, Dorota; Tabor, Piotr; Olszewska, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the paper is to estimate the prevalence of excess weight in the selected group of children growing up in different urban environments at the turn of preschool education and early education.
Keywords: overweight; obesity; urban environment; rural environment; child preschool; nadwaga; otyłość; dziecko wczesnoszkolne; środowisko wiejskie; środowisko miejskie